The analysis of translated literary irony: Some methodological issues - De Wilde, July (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
This article outlines some conceptual and methodological issues regarding the analysis of translated literary irony. In the first part it is argued that the TS scholar ’s adherence to a specific conception of literary irony is not value-free and entails programmatic consequences for TS research on translated irony. Only a dynamic approach to irony—where irony “happens” rather than “exists ”—allows us to embrace three relevant orientations in descriptive empirical TS research: (1) target-side functional investigations, (2) historical-descriptive oriented analyses and (3) translational interpretive oriented analyses. The second part focuses on three issues regarding the comparative ST-TT procedure, namely (1) the unit of comparison, (2) the degree of the differences looked upon and (3) the specific traits on the basis of which the differences and similarities are identified. The paper winds up with remarks on one kind of normativity inherent to the comparative procedure.